Computation of fast depressurization of water using a two-fluid model: Revisiting Bilicki modelling of mass transfer. (12th October 2017) - Lochon, H.; Daude, F.; Galon, P.; Hérard, J.-M.
Highlights: Fast depressurization of water is computed using a two-fluid seven-equation model. A new dynamic mass transfer relaxation time scale is proposed. The non-instantaneous relaxation hypothesis is assessed on four experiments. The ability of capturing metastable states is demonstrated. Abstract: This paper is devoted to the computation of the fast depressurization of water using a two-fluid model. Such application, which is extensively studied in the nuclear field, involves many interactions between two phenomena, the mass transfer and the propagation of pressure waves. A simple but physically-based modelling of the mass transfer for the depressurization of water is proposed, which relies on the work of Bilicki & Kestin [1] in the homogeneous frame. Four different experiments have been chosen to assess the proposed model. Three of them study the depressurization of hot water in a pressurized pipe. The comparison between converged numerical results and the experimental data shows a good agreement and demonstrates the ability of the two-fluid-model to capture the proper mass transfer for a wide range of thermodynamical conditions. The last test-case is the HDR experiment which considers the depressurization of a full-scale vessel under the hypothesis of a Loss Of Coolant Accident. The results of an ALE computation show the ability of the proposed model to retrieve experimental data in both structure and fluid.